2018
DOI: 10.1161/circoutcomes.117.003561
|View full text |Cite
|
Sign up to set email alerts
|

Improving Temporal Trends in Survival and Neurological Outcomes After Out-of-Hospital Cardiac Arrest

Abstract: Survival after OHCA has improved over time. This trend was associated with improved rates of bystander CPR, automated external defibrillator use, high-quality CPR metrics, and in-hospital targeted temperature management. The results suggest that multiple factors, each improving over time, may have contributed to the observed increase in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 29 publications
(62 reference statements)
0
61
0
1
Order By: Relevance
“…The Resuscitation Outcomes Consortium (ROC) was a North American multi-centre clinical research network designed to conduct clinical out-of-hospital trials of therapies for cardiac arrest and major trauma. Over a 10-year period, communities that participated in ROC observed a doubling of survival after OHCA [3,82]. This suggests that outcomes after OHCA can be improved, and that further investments in research and implementation warrant consideration.…”
Section: Future Directionsmentioning
confidence: 99%
“…The Resuscitation Outcomes Consortium (ROC) was a North American multi-centre clinical research network designed to conduct clinical out-of-hospital trials of therapies for cardiac arrest and major trauma. Over a 10-year period, communities that participated in ROC observed a doubling of survival after OHCA [3,82]. This suggests that outcomes after OHCA can be improved, and that further investments in research and implementation warrant consideration.…”
Section: Future Directionsmentioning
confidence: 99%
“…Resuscitation is attempted in around half of cases and return of spontaneous circulation (ROSC), at time of hospital transfer, is achieved in only 25.8% [2] . Reported estimates for survival to hospital discharge and favourable neurological outcomes are 9.4% and 8.5%, respectively [3] . Most survivors of OHCA achieve ROSC early in the resuscitation attempt [4] , whereas poor survival is typical for patients in whom ROSC is not achieved and transport to hospital with ongoing CPR is required [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The earliest targeted temperature era trended toward higher mortality (54.4% vs 42.9%, respectively), but this difference was not statistically significant (P ÂŒ 0.3649). Although our numbers are small in the contemporary era, this trend toward better outcomes has also been raised by Buick et al, 17 who recently showed improved survival over time from OHCA within the Toronto area; their factors associated with improved outcome over time include improved bystander cardiopulmonary resuscitation rate (CPR) rate and increased TTM use. 17 It is possible that the improved results from recent experience encompass a bundle of modern intensive care rather than solely the targeted temperature itself, but our setting has not changed significantly over time.…”
Section: Discussionmentioning
confidence: 86%
“…Although our numbers are small in the contemporary era, this trend toward better outcomes has also been raised by Buick et al, 17 who recently showed improved survival over time from OHCA within the Toronto area; their factors associated with improved outcome over time include improved bystander cardiopulmonary resuscitation rate (CPR) rate and increased TTM use. 17 It is possible that the improved results from recent experience encompass a bundle of modern intensive care rather than solely the targeted temperature itself, but our setting has not changed significantly over time. On the other hand, the TTM trial 5 also had some selection bias because of its randomized controlled design, and it is possible Severe cerebral disability: conscious, dependent on others for daily support because of impaired brain function.…”
Section: Discussionmentioning
confidence: 86%